Routes of administration for adeno-associated viruses carrying gene therapies for brain diseases - Zhou, Kai; Han, Jinming; Wang, Yafeng; Zhang, Yaodong; Zhu, Changlian (Frontiers in Molecular Neuroscience, 2022)
Gene therapy is a powerful tool to treat various central nervous system (CNS) diseases ranging from monogenetic diseases to neurodegenerative disorders. Adeno-associated viruses (AAVs) have been widely used as the delivery vehicles for CNS gene therapies due to their safety, CNS tropism, and long-term therapeutic effect. However, several factors, including their ability to cross the blood-brain barrier, the efficiency of transduction, their immunotoxicity, loading capacity, the choice of serotype, and peripheral off-target effects should be carefully considered when designing an optimal AAV delivery strategy for a specific disease. In addition, distinct routes of administration may affect the efficiency and safety of AAV-delivered gene therapies. In this review, we summarize different administration routes of gene therapies delivered by AAVs to the brain in mice and rats. Updated knowledge regarding AAV-delivered gene therapies may facilitate the selection from various administration routes for specific disease models in future research.